Politiche urbane e pratiche solidali durante la pandemia. Il panorama internazionale e un caso di studio - Agostini, Ilaria; Gisotti, Maria Rita (Scienze del Territorio, 2020)
The crisis triggered by Covid-19 has accelerated a process of rethinking of contemporary living forms, already underway for some time, started in recent years especially by the fight against climate change and by the movements for the ‘right to the city’. This contribution proposes a reflection on two levels: that of medium and long-term international urban policies, and that of solidarity practices experimented in the city of Florence, taken as a case study. The article therefore offers a critical summary of some international policy documents dedicated to the response of cities to Covid-19. In the part dedicated to the case study, it describes the emergence of self-organized solidarity networks created in response to the immediate needs of the inhabitants, excluded from institutional emergency measures. In conclusion, it is highlighted how the indications of European policies point towards a more inclusive, sustainable and digital city and towards a different model of tourist use. At the same time, it can be observed that convincing hypotheses for a territorial restart of strong political value come from the realities active in solidarity mutualism. At the basis of these visions lie, in our opinion, a renewed centrality of public policies and collective space, an ability for interinstitutional and cooperative dialogue with the various social components, an attention to the bioregional scale for an effective ecological transition.